2020 European guideline on the management of syphilis. (22nd October 2020) - Janier, M.; Unemo, M.; Dupin, N.; Tiplica, G.S.; Potočnik, M.; Patel, R.
Abstract: The 2020 edition of the European guideline on the management of syphilis is an update of the 2014 edition. Main modifications and updates include: ‐ The ongoing epidemics of early syphilis in Europe, particularly in men who have sex with men (MSM) ‐ The development of dual treponemal and non‐treponemal point‐of‐care (POC) tests ‐ The progress in non‐treponemal test (NTT) automatization ‐ The regular episodic shortage of benzathine penicillin G (BPG) in some European countries ‐ The exclusion of azithromycin as an alternative treatment at any stage of syphilis ‐ The pre‐exposure or immediate post‐exposure prophylaxis with doxycycline in populations at high risk of acquiring syphilis.